Epidemiology of Fatal Road Traffic Accidents in Iran, Yasouj, 2014-2015 - Tayebeh Rakhshani; Mansour Kashfi; Irandokht Amirian; Mohammad Reza Ebrahimi; Seyyed Saeed Hashemi Nazari (Shiraz University of Medical Sciences, 2018)
Introduction: Traffic accidents are considered a major public health problem in many parts of the world. The present study aimed to investigate the epidemiology of fatal traffic accidents in Yasouj city during the years 2014-2015. Methods: This descriptive-analytical study was carried out through a cross-sectional method and the study population included all individuals who had died in traffic accidents in Yasouj city during 2014-2015. The source of data collection was the Legal Medicine Organization. The data were analyzed through SPSS 16,using descriptive statistics and Chi-square test. Results: The mean age of the deceased was 35.44 ± 20.99 years. The highest death rate was observed in the age groups over 25-34 years old (21.3%), 15-24 years (17.6%) and 35-44 years (17%), respectively. Most of the deceased were male (75%), single (55.4%), illiterate (44%), self-employed (29.3%) and residents of rural areas (52.3%). The ultimate cause of death of more than half of the deceased was head trauma (30.7%) and most of the deceased had died at the accident site (55.4%). 52.7% had died of collision with a passenger car. There was a significant association between the location of death and location of accident (outside/inside)(p-value=0.004); also, the result showed no significant relationship between the cause of death and location of accident (p-value <0.001) and type of vehicle (p-value <0.001).